Plesiosaurs (Diapsida, sauropterygia) from Late Cretaceous (Late Campanian- Early maastrichtian) marginal marine environments from north Patagonia - O`Gorman, Jose Patricio (2015)
Fil: O`Gorman, Jose Patricio. División Paleontología Vertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina